2023
DOI: 10.1021/acsami.3c09434
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-Guided Crystallization of Oriented α-FAPbI3 Nanowire Arrays for Solar Cells

Aida Alaei,
Seyed Sepehr Mohajerani,
Ben Schmelmer
et al.

Abstract: Perovskite nanowire arrays with large surface areas for efficient charge transfer and continuous highly crystalline domains for efficient charge transport exhibit ideal morphologies for solar-cell active layers. Here, we introduce a room temperature two-step method to grow dense, vertical nanowire arrays of formamidinium lead iodide (FAPbI 3 ). PbI 2 nanocrystals embedded in the cylindrical nanopores of anodized titanium dioxide scaffolds were converted to FAPbI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…[26] Various methods to grow perovskite films with [001] preferential orientation have been demonstrated through additive engineering. [27][28][29][30] Additives with appropriate functional groups (e.g., carboxyl group (─COOH) and ammonium group (─NH 2 )) have the capacity to stabilize unbonded atoms on specific facets and modulate surface energy. [31,32] Lee et al reported that the addition of a precursor of 2D perovskite PEA 2 PbI 4 can induce growth in the [001] direction by controlling the surface energy of specific facets during the crystallization process.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Various methods to grow perovskite films with [001] preferential orientation have been demonstrated through additive engineering. [27][28][29][30] Additives with appropriate functional groups (e.g., carboxyl group (─COOH) and ammonium group (─NH 2 )) have the capacity to stabilize unbonded atoms on specific facets and modulate surface energy. [31,32] Lee et al reported that the addition of a precursor of 2D perovskite PEA 2 PbI 4 can induce growth in the [001] direction by controlling the surface energy of specific facets during the crystallization process.…”
Section: Introductionmentioning
confidence: 99%